Self-Efficacy in Children with Reading Disorder - Suganda, Marcelina Rizkyati; Nanik; Dianovinina, Ktut (ANIMA Indonesian Psychological Journal, 2011)
Nowadays early primary school children are demanded to be able to read well. This conditionbecomes a threat for those who are not ready or those who have reading disorder. The inability toread influences children’ psychological condition. The purpose of this study was to examinechildren’s self efficacy in those who have reading disorder. A quantitative and qualitativedescriptive approach was conducted to visualize psychotest data in which the quantitative datawas interpretated qualitatively. This study used two children 6-7 years of age who still could notread fluently. Results of this study show that self efficacy of those children is low. Factors thatbecome the cause of this condition are parent tolerance and indiscipline in educating theirchildren. Other factors that contribute to this low self efficacy are no successful experience, noappropriate modeling in learning as well as the important role of the child emotional factor. Dewasa ini anak sekolah dasar dituntut sudah mampu membaca dengan baik. Kondisi inimenjadi ancaman bagi mereka yang tak siap termasuk mereka yang menderita kesulitanmembaca. Ketakmampuan membaca memengaruhi kondisi psikologis anak. Tujuan penelitian iniadalah menggali keyakinan diri anak yang menyandang kesulitan membaca. Pendekatankuantitatif dan kualitatif dipakai untuk memvisualisasikan data psikotes dengan menginterpretasidata kuantitatif secara kualitatif. Studi ini mempelajari dua orang anak berusia 6-7 tahun yangbelum mampu membaca dengan lancar. Hasil studi ini menunjukkan bahwa keyakinan diri anak-anak tersebut rendah. Faktor yang menjadi penyebab kondisi ini adalah toleransi danketakdisiplinan orang tua dalam mendidik anaknya. Faktor lain yang berkontribusi padarendahnya keyakinan diri tersebut adalah mereka tak pernah mengalami keberhasilan bermakna,tak adanya pemodelan belajar yang tepat maupun peran penting faktor emosional anak.